Muslim Shrines in Palestine: The Case of Joseph's Shrine Through the eyes of Pre-Twentieth Century Voyagers, Geographers and Pilgrims - Al-Qobbaj, Amer A. (Journal of Holy Land and Palestine Studies, 2020)
This article presents a comprehensive and critical historical, architectural and cultural review of a Muslim Shrine in Palestine, known as Joseph's Shrine, located near the ancient Palestinian city of Shikmu (Shechem, Tell Balata), northeast of Nablus, Palestine. A key heritage site in Palestine, the current structure is constructed within the tradition of Islamic shrines in Palestine. The shrine consists of a cenotaph tomb, housed in a domed building, with an adjoining courtyard. The shrine has also been subject to architectural changes and restoration projects over the centuries, as evidenced in the writings of pilgrims, travellers and geographers visiting the region from the fourth to nineteenth centuries. The article argues that, while the remains of Joseph are not found at the site, the shrine itself is important within the religious and cultural heritage of Palestine, representing Ottoman-Islamic architectural aspects of this heritage.